AFRICAN MUSIC, A PEOPLE'S ART by Francis Bebey, George G. Harrap and Co. Ltd., London, 1975, viii + 184 pp., illustrations, discography, notes. Translated from ‘Musique de l'Afrique’ (Horizons de France, Paris 1969) by Josephine Bennett. - Dauer, A. M. (International Library of African Music, 1980)
pages: 129
Keywords: African Music